On structure and distances of some classes of repeated-root constacyclic codes over Galois rings - Hai Q. Dinh (2018)
© 2016 Elsevier Inc. The structure of λ-constacyclic codes of length 2 s over the Galois ring GR(2 a ,m) is obtained, for any unit λ of the form 4z−1, z∈GR(2 a ,m). The duals codes and necessary and sufficient conditions for the existence of a self-dual λ-constacyclic code are provided. Among others, this structure is used to establish the Hamming, homogeneous, and Rosenbloom–Tsfasman distances, and Rosenbloom–Tsfasman weight distribution of all such constacyclic codes.